Pengabdian Mahasiswa Kuliah Kerja Nyata Dalam Upaya Meningkatkan Desa Wisata Di Desa Berambai Makmur - Hidayati, Rusma; Febriyanta, Bayu; Setiawan, Rizky Fajar; Pramuditasari, Rosita; Puteri, Sabila Nadya; Adawiah, Robi’ah; Anisa, Salsa Bela; Suriansyah, Eka (Pakis Journal Institute, 2024)
This article discusses the Community Service Program (KKN) activities carried out by IAIN Palangka Raya students in Berambai Makmur Village. The activity aimed to increase community awareness about the potential of the tourist village and make a real contribution to the development of the village. The methods used in this service include direct observation and interaction with the community to identify problems and formulate appropriate solutions. Some of the activities carried out include making proposals for road infrastructure improvements, making alternative road signs, and developing tourist facilities such as ducks to attract visitors. In addition, students also contributed to social activities, such as hygiene socialization and making learning media for children at Uswatun Hasanah Kindergarten/TPA. The results of this service showed that KKN students succeeded in increasing the attractiveness of Berambai Makmur Village as a tourist destination and strengthening social relations between students and the local community. This activity is expected to provide long-term benefits for village development and improve the quality of life of the community.